AN ANALYSIS OF KWAME GYEKYE’S CONCEPTION OF ‘SUNSUM’ IN AKAN PHILOSOPHY - Majeed, Hasskei M. (Ghana journal of religion and theology, 2017)
The concept of sunsum has been a subject of disagreement among Akan philosophers. Gyekye criticizes the views of Akan writers such as Kofi Busia, Joseph Danquah and Kwasi Wiredu despite his acceptance of their position that sunsum is the basis of an individual’s personality. This paper examines Gyekye’s critique of these authors (especially Busia) and shows how Gyekye’s arguments are not only sometimes inaccurate, but also how they do generate a major problem of attribution that hampers a good understanding of his thesis.